Bifunctional activation of amine-boranes by the W/Pd bimetallic analogs of "frustrated Lewis pairs". Issue 10 (28th January 2021) - Osipova, Elena S.; Gulyaeva, Ekaterina S.; Gutsul, Evgenii I.; Kirkina, Vladislava A.; Pavlov, Alexander A.; Nelyubina, Yulia V.; Rossin, Andrea; Peruzzini, Maurizio; Epstein, Lina M.; Belkova, Natalia V.; Filippov, Oleg A.; Shubina, Elena S.
Abstract : Bimetallic complexes [LW(CO)2 (μ-CO)⋯Pd(PCP)] cooperatively activate amine-boranes for their dehydrogenation via N–H proton tunneling at RDS and H2 evolution from two neutral hydrides. Abstract : The reaction between basic [(PCP)Pd(H)] (PCP = 2, 6-(CH2 P( t -C4 H9 )2 )2 C6 H4 ) and acidic [LWH(CO)3 ] (L = Cp (1a ), Tp (1b ); Cp = η 5 -cyclopentadienyl, Tp = κ 3 -hydridotris(pyrazolyl)borate) leads to the formation of bimolecular complexes [LW(CO)2 (μ-CO)⋯Pd(PCP)] (4a, 4b ), which catalyze amine-borane (Me2 NHBH3, t BuNH2 BH3 ) dehydrogenation. The combination of variable-temperature ( 1 H, 31 P{ 1 H}, 11 B NMR and IR) spectroscopies and computational (ωB97XD/def2-TZVP) studies reveal the formation of an η 1 -borane complex [(PCP)Pd(Me2 NHBH3 )] + [LW(CO3 )] − (5 ) in the first step, where a BH bond strongly binds palladium and an amine group is hydrogen-bonded to tungsten. The subsequent intracomplex proton transfer is the rate-determining step, followed by an almost barrierless hydride transfer. Bimetallic species 4 are easily regenerated through hydrogen evolution in the reaction between two hydrides.